Conventional antidiabetic agents and bone health: A pilot case–control study - Jeffrey Pradeep Raj; Shreeraam Venkatachalam; Mahesh Shekoba; Joshua Jonathan Norris; Rajkumar S Amaravati (Perspectives in Clinical Research, 2019)
Background and Objectives: The burden of noncommunicable diseases such as diabetes (type 2 diabetes mellitus [T2DM]) and osteoporosis is increasing with increasing longevity. Uncontrolled T2DM is an independent risk factor for osteoporosis explained by the insulin osteocalcin pathway. Due to limited information on the effect of various commonly used antidiabetic agents (ADA) on bone health, our study aims to analyze the association between the two. Methodology: This is a case–control study, with 100 cases of clinical osteoporosis and 100 age-, sex-, and dietary status-matched controls in whom osteoporosis was ruled out by dual-energy X-ray absorptiometry scan. Prescription details of T2DM, physical activity levels, and disease status were collected using a pretested questionnaire. Exposure to each ADA was compared using the Chi-squared test. Binary logistic regression was performed to adjust the two main confounders, namely glycemic control and physical activity levels, and adjusted risk estimates were calculated. Results: There were a total of 74 T2DM patients, of whom 45 (60.8%) were cases and 29 (39.2%) were controls. Sulfonylureas (adjusted odds ratio [aOR] = 0.164, P = 0.004) and insulin (aOR = 0.248, P = 0.042) showed a significant protective effect on bone health. Biguanides (OR = 1.994, P = 0.029) and thiazolidinediones (OR: 5.444, P = 0.033), which demonstrated that an increased risk of osteoporosis in univariate analysis became insignificant after multivariate analysis. Conclusion: Sulfonylureas and insulin through the insulin osteocalcin pathway show favorable effect on bone health, but the probability of increased fractures secondary to hypoglycemic falls should be borne in mind. We recommend larger prospective studies to confirm this association.